Semi-fragile watermark for sensor data. (1st January 2011) - Kamel, Ibrahim; AlKoky, Osama
This paper proposes a novel semi-fragile watermarking technique for sensor data. The proposed watermarking technique embeds the secret watermark in the order of the data readings rather than the data values themselves, thus, does not cause distortion to the transmitted data values. Transmitted data readings are organised in groups of fixed length. The watermarking algorithm then reorders data readings relative to each other according to the value of the secret watermark. The proposed scheme tolerates minor changes that might be caused by channel error. In case of a single attack, the proposed technique can identify the victim element with high probability. The paper provides detailed security analysis to show the robustness of the proposed techniques against various types of attacks. Extensive experiments are performed to measure the attack detection and victim identification rate. The execution time of the watermark embedding and integrity check is also shown.